Terminal Ileum Perforation: A Rare Complication of Verocytotoxigenic Escherichia coli Infection in an Adult With Prader-Willi Syndrome. (December 2021) - Duffy, Michael; Kesha, Kilak; Glenn, Charley; Stables, Simon; Tse, Rexson Datquen
Abstract : Abstract: Intestinal perforation is an uncommon complication and presentation of verocytotoxigenic Escherichia coli (VTEC) infection in individuals with Prader-Willi syndrome (PWS). The common site of perforation from VTEC infection is in the colon (and almost exclusively in the pediatric population), whereas PWS is in the stomach. Terminal ileum perforation is uncommon and is not reported in either these 2 conditions. We report a death from terminal ileum perforations in an adult who had PWS and was infected with VTEC. Potential reasons why the perforation occurred at this rare location, rather than in other more common location, in an adult are discussed.